Pengaruh Likuiditas dan Profitabilitas Terhadap Harga Saham Melalui Nilai Perusahaan Sebagai Variabel Intervenng pada Perusahaan Sektor Barang dan Konsumsi di Bursa Efek Indonesia Tahun 2016-2020 - Fitria, Marlina; Chandrayanti, Teti; Lady Silvera, Dica (Ekasakti Pareso Jurnal Akuntansi, 2024)
This research aims to prove and analyze the influence of liquidity and profitability on share prices through company value as an intervening variable in consumption sector companies on the Indonesia Stock Exchange. In this research, the companies used were companies in the goods and consumption sector which were selected using a purposive sampling method. The data used was from 2016 to 2020. The data processing was carried out using the help of the Eviews program. In this research, indirect influence testing with intervening variables was carried out using the Sobel Test method. Based on the results of testing the hypothesis, it was found that company liquidity had no significant effect on the share prices of companies in the goods and consumption sector on the Indonesia Stock Exchange. In testing the second hypothesis, it was found that company profitability had a significant effect on the share prices of companies in the goods and consumption sector on the Indonesia Stock Exchange. testing the third hypothesis, it was found that company value had a significant effect on the share prices of companies in the goods and consumption sector on the Indonesian Stock Exchange.